Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes Russia's fiscal framework and the oil-price shock. Russia has relied heavily on its abundant natural resource wealth to finance fiscal deficits since the global financial crisis in 2008-09. The pace of adjustment of the oil-price benchmark could be increased by including future prices in its calculation. Although converting oil revenues using a backward-looking average of the exchange rate could also lead to a more rapid fiscal adjustment, it also implies additional technical and communication challenges. In addition, the fiscal anchor could be more ambitious to safeguard intergenerational equity. Expressing the fiscal rule in terms of a minimum 'structural" balance could promote greater savings.